Intermittent hypoxia-induced downregulation of microRNA-320b promotes lung cancer tumorigenesis by increasing CDT1 via USP37 - Weihao Li; Kai Huang; Fengbiao Wen; Guanghui Cui; Haizhou Guo; Zhanfeng He; Song Zhao (Elsevier, 2021)
Obstructive sleep apnea-hypopnea (OSAH) is correlated with an increased incidence of lung cancer. In our study, we explored the functional roles of microRNAs (miRNAs) in lung cancer patients that were complicated with OSAH involving the deubiquitination enzyme. The miR-320b expression pattern in lung cancer tissues and cells was determined. The interactions between ubiquitin-specific peptidase 37 (USP37) and miR-320b were evaluated by a dual-luciferase reporter gene assay, whereas USP37 and Cdc10-dependent transcript 1 (CDT1) was assessed by co-immunoprecipitation and immunofluorescence. After the induction of intermittent hypoxia (IH), a gain-of function approach was performed to investigate roles of miR-320b, USP37, and CDT1 in lung cancer cell proliferation and invasion. In addition, nude mouse xenograft models were used to study their effects on tumor growth in vivo. miR-320b was poorly expressed in lung cancer patients with OSAH. IH treatment downregulated the expression of miR-320b but promoted the proliferation and invasion capabilities of lung cancer cells, both of which were suppressed by the overexpression of miR-320b through decreasing USP37. USP37 interacted with and deubiquitinated CDT1 to protect it from proteasomal degradation. Our study uncovered that IH-induced downregulation of miR-320b promoted the tumorigenesis of lung cancer by the USP37-mediated deubiquitination of CDT1.